Resolution of acyclovir‐associated neurotoxicity with the aid of improved clearance estimates using a Bayesian approach: A case report and review of the literature. (29th March 2017) - Watson, W. A.; Rhodes, N. J.; Echenique, I. A.; Angarone, M. P.; Scheetz, M. H.
Summary: What is known and objective: Neurotoxicity is a side effect of acyclovir. We report the first case, to our knowledge, whereby Bayesian‐informed clearance estimates supported a therapeutic intervention for acyclovir‐associated neurotoxicity. Case summary: A 62‐year‐old male with the diagnosis of disseminated zoster was being treated with intravenous (IV) acyclovir when he developed symptoms of acute neurotoxicity. Acyclovir had been dose‐adjusted for renal dysfunction according to traditional creatinine clearance estimates; however, as the patient was also on vancomycin, Bayesian estimates of vancomycin clearances were performed, which revealed a 2‐fold lower creatinine clearance. In response to the Bayesian estimates, acyclovir was discontinued, and improvements in mentation were noted within 24 hours. What is new and conclusion: Alternate approaches to estimate renal function beyond Cockcroft‐Gault, such as a Bayesian approach used in our patient, should be considered when population estimates are likely to be inaccurate and potentially dangerous to the patient. Abstract : Neurotoxicity is a known adverse effect of acyclovir. We report the first case, to our knowledge, whereby Bayesian‐informed clearance estimates supported a therapeutic intervention for acyclovir‐associated neurotoxicity. Bayesian estimates of vancomycin clearance were performed and revealed a 2‐fold lower estimate of renal function than creatinine clearance estimates. Acyclovir was discontinued based on vancomycin clearance estimates, and improvements in mentation were noted within 24 hours.